Molecular dynamic simulation: Studying the effects of Brownian motion and induced micro-convection in nanofluids. (18th March 2016) - Lee, S. L.; Saidur, R.; Sabri, M. F. M.; Min, T. K.
ABSTRACT: Nanofluids are suspensions of nanoparticles into convectional heat transfer fluid to enhance the thermal conductivity of its base fluid. The roles of Brownian motion of nanoparticles and induced micro-convection in base fluid in enhancing the thermal conductivity of nanofluids were investigated using molecular dynamic (MD) simulation. The roles were determined by studying the effect of particle size on thermal conductivity and diffusion coefficient. Results show that the Brownian motion and induced micro-convection have insignificant effects on enhancing the thermal conductivity. The hydrodynamic effect is restricted by an amorphous-like interfacial fluid structure in the vicinity of the nanoparticle due to its higher specific area.